Early Repolarization Syndrome: Electrocardiographic Signs and Clinical Implications - Rezus, Ciprian (Ann Noninvasive Electrocardiol, 2013)
Early repolarization syndrome (ERS) was previously considered as a benign variant, but it has recently emerged as a risk marker for idiopathic ventricular fibrillation (VF) and sudden death. As measured by electrocardiogram (ECG), early repolarization is characterized by an elevation of the J point and/or ST segment from the baseline by at least 0.1 mV in at least two adjoining leads. In particular, early repolarization detected by inferior ECG leads was found to be associated with idiopathic VF and has been termed as ERS. This condition is mainly observed in young men, athletes, and blacks. Also, it has become evident that electrocardiographic territory, degree of J‐point elevation, and ST‐segment morphology are associated with different levels of risk for subsequent ventricular arrhythmia. However, it is unclear whether J waves are more strongly associated with a depolarization abnormality rather than a repolarization abnormality. Several clinical entities can cause ST‐segment elevation. Therefore, clinical and ECG data are essential for differential diagnosis. At present, the data set is insufficient to allow risk stratification in asymptomatic individuals. ERS, idiopathic VF, and Brugada syndrome (known as J‐wave syndromes) are three clinical conditions that share many common ECG features; however, their clinical consequences are remarkably different. This review summarizes the current electrocardiographic data concerning ERS with clinical implications.